Don’t Be a Blockhead: Zoned Namespaces Make Work on Conventional SSDs Obsolete - Stavrinos, Theano; Berger, Daniel S.; Katz-Bassett, Ethan; Lloyd, Wyatt (HotOS, 2021)
Research on flash devices almost exclusively focuses on conventional SSDs, which expose a block interface. Industry, however, has standardized and is adopting Zoned Namespaces (ZNS) SSDs, which offer a new storage interface that dominates conventional SSDs. Continued research on conventional SSDs is thus a missed opportunity to unlock a step-change improvement in system performance by building on ZNS SSDs. We argue for an immediate and complete shift in research to ZNS SSDs and discuss research directions.